2019
DOI: 10.1128/jcm.00945-19
|View full text |Cite
|
Sign up to set email alerts
|

Increased Clinical Specificity with Ultrasensitive Detection of Clostridioides difficile Toxins: Reduction of Overdiagnosis Compared to Nucleic Acid Amplification Tests

Abstract: Clostridioides difficile infection (CDI) is one of the most common health care-associated infections, resulting in significant morbidity, mortality, and economic burden. Diagnosis of CDI relies on the assessment of clinical presentation and laboratory tests. We evaluated the clinical performance of ultrasensitive single-molecule counting technology for detection of C. difficile toxins A and B. Stool specimens from 298 patients with suspected CDI were tested with the nucleic acid amplification test (NAAT; BD MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…It could have been impacted by the differences in limits of detection between CCNA and Clarity, as CCNA has an estimated limit of detection of 50 to 100 pg/ml and Clarity has a cutoff of 12 pg/ml (21). The Clarity assay showed higher specificity than PCR while maintaining acceptable sensitivity (78 to 96%), which has been supported by other studies (11,(22)(23)(24). Predictably, specificity was reduced while sensitivity was improved for tests that detect the presence of either toxin genes or C. difficile antigens ( Table 1).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It could have been impacted by the differences in limits of detection between CCNA and Clarity, as CCNA has an estimated limit of detection of 50 to 100 pg/ml and Clarity has a cutoff of 12 pg/ml (21). The Clarity assay showed higher specificity than PCR while maintaining acceptable sensitivity (78 to 96%), which has been supported by other studies (11,(22)(23)(24). Predictably, specificity was reduced while sensitivity was improved for tests that detect the presence of either toxin genes or C. difficile antigens ( Table 1).…”
Section: Discussionsupporting
confidence: 61%
“…Because the NAAT is a highly sensitive test, it may lead to the overdiagnosis of CDI if used in an inappropriate setting, as it can be positive in both infection and colonization (2). An ultrasensitive assay may further reduce overdiagnosis of CDI if robust screening is implemented and improper stool collection is minimal (24).…”
Section: Discussionmentioning
confidence: 99%
“…CDI is a toxin-mediated disease; due to the high incidence of both diarrhea and colonization in tested populations, the detection of toxigenic organisms leads to overdiagnosis and overtreatment (7,18,19). In a recent study, it was shown that presence of toxins, as measured with the Clarity assay, correlated with CDI relapse, death, and severity of disease and that the proportion of CDI overdiagnosis was more than three times higher in NAAT ϩ /toxin Ϫ than in NAAT ϩ /toxin ϩ patients (14). Use of the Clarity ultrasensitive toxin assay improved clinical specificity compared with that of NAAT, without the poor sensitivity shown by contemporary toxin EIAs (14).…”
Section: Discussionmentioning
confidence: 99%
“…Singulex Clarity C. diff toxins A/B assay. The Clarity assay detects C. difficile toxins A and B in stool on the Singulex Clarity system, as has been described previously (11)(12)(13)(14). Briefly, either 100 l of a liquid or semisolid or 0.1 g (not tested in this study) of a solid stool sample is mixed (1:20) with diluent buffer and centrifuged at 14,000 ϫ g for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Higher toxin concentrations have been reported in PCR ribotype 027 than in non-027 strains (25), but there was no difference in toxin concentration between multiple non-027 ribotype strains (35). Although a correlation between toxin concentrations and CDI severity has been observed (47) and high concentrations have been reported in individual patients with severe disease and ileus (32,36), the lack of such a correlation has also been reported (9,24,41,42). LoD (27) or cutoff (9,26) in that range may be too high and will lead to missed cases.…”
Section: Correlation With Disease: What Specificity Can Be Achieved?mentioning
confidence: 99%